Multilingual Signs: The Linguistic Landscape in Nusa Dua Tourist Area, Bali - Rastitiati, Ni Kade Juli; Suprastayasa, I Gusti Ngurah Agung (LACULTOUR: Journal of Language and Cultural Tourism, 2022)
This research aimed at finding out and describing the profile of linguistic lanscape, namely the languages used in the informational signs in Nusa Dua, Bali tourist destination. These signs can include information boards, warning boards, prohibition board, and boards for the name of hotels, buildings, restaurants, food courts, spa, shopping center and hospital. This research was a qualiatative in nature through describing the languages used in the tourist destination. The data was obtained by means of handphone camera, and about 116 visual pictures were collected. The results showed that there are 8 (eight) variations in the use of languages in the linguistic landscape in Nusa Dua, Bali tourist destination. The eight variations were: 1) Indonesian 2). English, 3). bilingual Indonesian and English, 4). bilingual English and Indonesian, 5). bilingual Balinese and English, 6). multilingual Balinese, Indonesian and English, 7). multilingual Japanese, English, Chinese and Korean, and 9) multilingual Balinese, English, Japanese, Chinese. Russian, Hindi, Jerman, Korean, Indonesia and French